Importance Of Using Generative AI In Education: Dawn of a New Era - Rajendran, Rajashree Manjulalayam (Journal of Science & Technology, 2023)
The teaching methodology has witnessed a paradigm shift by incorporating advanced technologies. The modern world offers a whole new insight into the mental well-being of students. This transformation has opened new doors that are eye-opening for the human mind.The invention of artificial intelligence (AI) in the modern world has helped solve and detect problems. Among all these developments, one has shifted the standard of the educational world. It has taken over the old methods and techniques the students did not previously appreciate. This technology, the Generative Artificial Intelligence (GAI), has altered the orthodox educational approaches. It has provided a potential benefit for delivering knowledge in the best direction, enabling students to understand and implement it in their lives.Therefore, this paper significantly focuses on the impact of Generative Artificial Intelligence (GAI) technology in providing protection and assistance in the education system. It has contributed value and principles to the revolution of the modern education system. The data declared in the paper was taken from effective sources and proved to favor the study.
Keywords: Generative Artificial Intelligence; GAI; modern world; education; orthodox